Análisis e implementación de tecnologías MOOCS " Masive Open Online Course" para el fortalecimiento académico de la carrera de ingeniería en sistemas y computación. - Duchi Ushca, Johana Lised (2016)
The National University of Chimborazo is an institution that provides the opportunity for training people of all ages, educational processes performed individually or in groups through face tutorials. These academic processes have been basing text guide the same as after tutoring becomes the only tool of self-learning, Career Systems Engineering and Computer when no offer virtual online courses as currently are so necessary for a motivating and collaborative learning. Consequently, this project determines the analysis and implementation of technologies MOOCs "Massive Open Online Course" for the contribution of academic strengthening of Career Systems and Computer Engineering. After implementing the MOOCs technologies in academic activities proceeded to verify the hypothesis by statistical test Chi Square, resulting in the online course for students was a contribution to academic strengthening giving a positive response to the performance of virtual environments variety of resources that integrate and motivate the student to investigate and work on the development of training. In the end it concludes that it is appropriate to implement these technologies in educational institutions and mentoring support to ease time and space student and innovate the teaching-learning through ICT.